An archaeological study of the Zimbabwe culture capital of Khami, south-western Zimbabwe - Mukwende, Tawanda (Department of Archaeology, 2017)
This study sought to understand the archaeology of the Zimbabwe Culture capital of Khami through synchronic and diachronic analyses of its material culture. The research employed a number of methodological approaches that included a review of historic documents, surveying and mapping, excavations, museum collection analysis, and artefact studies, in order to collect datasets from various sections of the site, including the walled and the nonwalled areas. The main indication is that there is a great deal of similarity in material culture distribution across the whole site. An analysis of objects by stratigraphic sequence exposes continuity and change in local and imported objects. Dry stone-wall architectural data suggests that the site was constructed over a long period, with construction motivated by a number of expansionary factors. The study confirms that Khami began as a fully developed cultural unit, with no developmental trajectory recorded at Mapungubwe or Great Zimbabwe, where earlier ceramic units influenced later ones. Consequently, this study cautiously suggests that Khami represents a continuity with the Woolandale chiefdoms that settled in the south-western parts of the country and in the adjacent areas of Botswana. On the basis of the chronological and material culture evidence, Khami is unlikely to have emerged out of Great Zimbabwe. However, more research is needed to confirm these emergent conclusions, and to better understand the chronological and spatial relationships between not just Woolandale and Khami sites but also Khami and the multiple Khami-type sites scattered across southern Zambezia.